Microcrystallization test method for amorphous PETG copolyester
By dissolving amorphous PETG copolyester in hexafluoroisopropanol and performing methanol precipitation treatment, the problem of difficulty in detecting the microcrystalline nature of PETG in the prior art is solved, and the effect of efficient detection of the microcrystalline nature of PETG through differential scanning calorimetry is achieved.
Patent Information
- Application Number
- CN202510007930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to quickly and effectively detect the microcrystalline properties of amorphous PETG copolyesters, resulting in the inability to analyze their crystallization properties.
By dissolving amorphous PETG copolyester in hexafluoroisopropanol and precipitating with methanol, a test sample that can reflect the microcrystalline properties was obtained, and then the detection was performed using differential scanning calorimetry.
This method can effectively release the microcrystalline information of PETG, improve the symmetry and regularity of its molecular chain spatial structure, so that conventional differential scanning calorimeters can observe the microcrystalline information of PETG from scratch, which is simple and efficient.
Smart Images

Figure CN119757458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of analysis and detection, in particular to a micro-crystallization testing method for amorphous PETG copolyester. Background Art
[0002] Polyethylene terephthalate (PET) is a commonly used thermoplastic resin, widely used in the fields of fiber, film and packaging materials, especially in the production of beverage bottles. However, it has a slow crystallization rate at normal temperature, and crystallization occurs when heated, which has an adverse effect on the dimensional stability and transparency of the formed products. PETG copolyester is a non-crystalline copolyester material, which is mainly formed by the reaction of terephthalic acid and ethylene glycol, in which part of the ethylene glycol is replaced by a third monomer such as cyclohexanedimethanol (CHDM) or neopentyl glycol (NPG). It is a transparent, non-crystalline copolyester, thus overcoming the defects of PET in this regard.
[0003] However, in actual applications, PETG still appears white and foggy when used as cosmetic bottles, drinking water bottles, etc. Therefore, it can be seen that PETG also has microscopic crystals.
[0004] In the prior art, DSC, XRD and other detection methods are important means of testing the crystallinity of polyester products. However, the DSC curve of PETG does not show crystallization and melting peaks, and the XRD sensitivity cannot test microcrystallization, which means that the crystallinity of amorphous PETG cannot be analyzed and detected. However, actual application scenarios have proved that PETG exists in a microcrystalline state. Therefore, it is urgent to establish a test method that can quickly test the microcrystallization of amorphous PETG copolyester.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a microcrystallization test method for amorphous PETG copolyester, which can effectively release microscopic crystallinity information, and while removing small molecules, it can also ensure that PETG has enough freedom and energy to readjust the molecular chain spatial structure in the process, improve symmetry and regularity, thereby reflecting microscopic crystallinity. At the same time, the test method of the present application can observe the microscopic crystallinity information of PETG from scratch through a conventional differential scanning calorimeter, which is simple and efficient, and is more innovative and practical than the methods used in the prior art.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] The present invention provides a method for testing microcrystallization of amorphous PETG copolyester, the testing method comprising:
[0009] Pre-treating the amorphous PETG copolyester to obtain a test sample that can reflect the microcrystalline performance of the amorphous PETG copolyester, and then testing the test sample using differential scanning calorimetry;
[0010] The pre-treatment method comprises: dissolving amorphous PETG copolyester in hexafluoroisopropanol, and then precipitating with methanol.
[0011] Furthermore, the pre-treatment comprises the following steps:
[0012] Amorphous PETG copolyester is added to hexafluoroisopropanol, and then heated to dissolve to obtain solution A; methanol is added to solution A to obtain a polymer precipitate; the polymer precipitate is dried to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
[0013] Furthermore, the material-liquid ratio of amorphous PETG copolyester to hexafluoroisopropanol in the solution A is: 0.5-1.5:5-15 g / ml.
[0014] Furthermore, the temperature of the heating dissolution is 50° C. and the time is 1 hour.
[0015] Furthermore, the volume ratio of the added amount of methanol to solution A is 10:5-15.
[0016] Furthermore, the drying temperature of the polymer precipitation is 100° C. and the drying time is 2 hours.
[0017] Furthermore, the pre-treatment comprises the following steps:
[0018] (A) adding amorphous PETG copolyester to hexafluoroisopropanol at a material-liquid ratio of 0.5-1.5:5-15 g / ml, and then heating and dissolving at 50° C. for 1 h to obtain solution A;
[0019] (B) Methanol is added to solution A at a volume ratio of 10:5 to 15, and the mixture is stirred to obtain a solution containing a polymer precipitate, and the solid-liquid separation is performed. The polymer precipitate is dried at 100° C. for 2 h to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
[0020] Furthermore, the detection method of the differential scanning calorimetry includes:
[0021] The test sample was tested using a differential scanning calorimeter, and then the crystallinity of the test sample was calculated based on the melting peak and melting peak area of the test sample.
[0022] Furthermore, the calculation formula for the crystallinity of the test sample is:
[0023] Crystallinity = melting peak area / theoretical enthalpy of crystalline material*100%.
[0024] Furthermore, in the differential scanning calorimetry, the temperature is 30-300° C. and the heating rate is 10° C. / min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a microcrystallization test method for amorphous PETG copolyester, the test method comprising: pre-treating the amorphous PETG copolyester to obtain a test sample that can reflect the microcrystallization performance of the amorphous PETG copolyester, and then using differential scanning calorimetry to detect the test sample; wherein: the pre-treatment method comprises: dissolving the amorphous PETG copolyester in hexafluoroisopropanol, and then using methanol for precipitation. The present invention can effectively release microscopic crystallinity information by using a pre-treatment method of hexafluoroisopropanol dissolution and methanol precipitation to treat the amorphous PETG copolyester, while removing small molecules, it can also ensure that PETG has enough freedom and energy in this process to readjust the spatial structure of the molecular chain, improve symmetry and regularity, thereby reflecting microscopic crystallinity. In addition, the pre-treated test sample can observe the microscopic crystallinity information of PETG from scratch using a conventional differential scanning calorimeter, which is simple and efficient, and is more innovative and practical than the method used in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The result diagram of direct differential scanning calorimetry testing of 11 amorphous PETG copolyester samples provided in Test Example 1 of the present invention;
[0029] Figure 2 This is a graph showing the results of differential scanning calorimetry testing of 11 amorphous PETG copolyester samples obtained by testing in the testing method of Example 1 provided in Test Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] According to one aspect of the present invention, a method for testing microcrystallization of amorphous PETG copolyester comprises: pre-treating the amorphous PETG copolyester to obtain a test sample that can reflect the microcrystallization performance of the amorphous PETG copolyester, and then testing the test sample using differential scanning calorimetry;
[0033] The pre-treatment method comprises: dissolving amorphous PETG copolyester in hexafluoroisopropanol, and then precipitating with methanol.
[0034] The present invention provides a microcrystallization test method for amorphous PETG copolyester, the test method comprising: pre-treating the amorphous PETG copolyester to obtain a test sample that can reflect the microcrystallization performance of the amorphous PETG copolyester, and then using differential scanning calorimetry to detect the test sample; wherein: the pre-treatment method comprises: dissolving the amorphous PETG copolyester in hexafluoroisopropanol, and then using methanol for precipitation. The present invention can effectively release microscopic crystallinity information by using a pre-treatment method of hexafluoroisopropanol dissolution and methanol precipitation to treat the amorphous PETG copolyester, while removing small molecules, it can also ensure that PETG has enough freedom and energy in this process to readjust the spatial structure of the molecular chain, improve symmetry and regularity, thereby reflecting microscopic crystallinity. In addition, the pre-treated test sample can observe the microscopic crystallinity information of PETG from scratch using a conventional differential scanning calorimeter, which is simple and efficient, and is more innovative and practical than the method used in the prior art.
[0035] In a preferred embodiment of the present invention, the pre-treatment comprises the following steps:
[0036] Amorphous PETG copolyester is added to hexafluoroisopropanol, and then heated to dissolve to obtain solution A; methanol is added to solution A to obtain a polymer precipitate; the polymer precipitate is dried to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
[0037] In a preferred embodiment of the present invention, the material-liquid ratio of amorphous PETG copolyester to hexafluoroisopropanol in the solution A is: 0.5-1.5:5-15 g / ml.
[0038] As a preferred embodiment, the liquid-to-material ratio of the amorphous PETG copolyester to hexafluoroisopropanol has a better dissolving effect. If the mass of the amorphous PETG copolyester is too large, the time required for dissolution should be extended or the temperature for heating to promote dissolution should be increased, which may eventually cause the sample to be unable to be completely dissolved; if the proportion of hexafluoroisopropanol is too large, it is likely to cause incomplete methanol precipitation, and more sample components are taken away by hexafluoroisopropanol and cannot be precipitated and crystallized, resulting in distorted results.
[0039] In a preferred embodiment of the present invention, the temperature of heating and dissolving is 50° C. and the time is 1 hour.
[0040] In a preferred embodiment of the present invention, the volume ratio of the added amount of methanol to solution A is 10:5-15.
[0041] As a preferred embodiment, the above-mentioned methanol addition amount according to the above ratio has a better precipitation effect. If the amount of methanol added is insufficient, more samples will still be dissolved in hexafluoroisopropanol and cannot be effectively precipitated and crystallized; adding too much generally has no effect on the results, but will waste a lot of methanol solvent.
[0042] In a preferred embodiment of the present invention, the drying temperature of the polymer precipitate is 100° C. and the drying time is 2 hours.
[0043] In a preferred embodiment of the present invention, the pre-treatment comprises the following steps:
[0044] (A) adding amorphous PETG copolyester to hexafluoroisopropanol at a material-liquid ratio of 0.5-1.5:5-15 g / ml, and then heating and dissolving at 50° C. for 1 h to obtain solution A;
[0045] (B) Methanol is added to solution A at a volume ratio of 10 ml:5-15 ml, and the mixture is stirred to obtain a solution containing a polymer precipitate, and the solid-liquid separation is performed. The polymer precipitate is dried at 100° C. for 2 h to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
[0046] In a preferred embodiment of the present invention, the detection method of differential scanning calorimetry comprises:
[0047] The test samples were tested using a differential scanning calorimeter, and the crystallinity of the test samples was then calculated based on the melting peak temperature and melting peak area of the test samples.
[0048] In the above preferred embodiment, the calculation formula of the crystallinity of the test sample is:
[0049] Crystallinity = melting peak area / theoretical enthalpy of crystalline material*100%.
[0050] In a preferred embodiment of the present invention, in the differential scanning calorimetry, the temperature is 30-300° C., and the heating rate is 10° C. / min.
[0051] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0052] Example 1
[0053] A method for testing microcrystallization of amorphous PETG copolyester, the testing method comprising the following steps:
[0054] 1. Sampling: Accurately weigh 1.0 g of amorphous PETG copolyester sample and add 10 mL of hexafluoroisopropanol.
[0055] 2. Sample dissolution: Place on a heating plate and heat at 50°C for 1 hour and shake occasionally, then heat to 50°C and shake occasionally until completely dissolved, remove and let stand to cool to room temperature.
[0056] 3. Sample precipitation: Add 10 mL of methanol and mix thoroughly to precipitate the PETG polymer.
[0057] 4. Sample drying: Take out the precipitate and dry it in an oven at 100°C for 2 hours.
[0058] 5. Detection: Take 5-10 mg of sample and test it in differential scanning calorimeter. The instrument parameter settings of differential scanning calorimeter are as follows:
[0059] Set purge gas 1 (air): 0 mL / min if not turned on; purge gas 2 (nitrogen) 40 mL / min; protective gas (nitrogen) 60 mL / min;
[0060] Temperature program: initial temperature 30 °C, heating to 300 °C at 10 °C / min, one-time heating.
[0061] 6. Data processing: According to the melting peak temperature and its area, the crystallinity is calculated according to the following formula.
[0062] Xc = melting peak area / theoretical enthalpy of crystalline material*100%.
[0063] Note: Xc is the crystallinity of the sample at different temperatures, and the theoretical enthalpy of the crystalline material is 140 J / g based on PET.
[0064] Example 2
[0065] A method for testing microcrystallization of amorphous PETG copolyester, the testing method comprising the following steps:
[0066] 1. Sampling: Accurately weigh 0.5 g of sample and add 15 mL of hexafluoroisopropanol.
[0067] 2. Sample dissolution: Place on a heating plate and heat at 50°C for 1 hour and shake occasionally, then heat to 80°C and shake occasionally until completely dissolved, remove and let stand to cool to room temperature.
[0068] 3. Sample precipitation: Add (10-20) mL of methanol and mix thoroughly to precipitate the PETG polymer.
[0069] 4. Sample drying: Take out the precipitate and dry it in a 120℃ oven for 0.5h.
[0070] 5. Detection: Same as Example 1.
[0071] 6. Data processing: same as in Example 1.
[0072] Example 3
[0073] A method for testing microcrystallization of amorphous PETG copolyester, the testing method comprising the following steps:
[0074] 1. Sampling: Accurately weigh 1.5 g of sample and add 5 mL of hexafluoroisopropanol.
[0075] 2. Sample dissolution: Place on a heating plate and heat at 50°C for 1 hour and shake occasionally, then heat to 100°C and shake occasionally until completely dissolved, remove and let stand to cool to room temperature.
[0076] 3. Sample precipitation: Add (10-20) mL of methanol and mix thoroughly to precipitate the PETG polymer.
[0077] 4. Sample drying: Take out the precipitate and place it in a 150℃ oven to dry for 1 hour.
[0078] 5. Detection: Same as Example 1.
[0079] 6. Data processing: same as in Example 1.
[0080] Test Example 1
[0081] (I) Eleven amorphous PETG copolyester samples were selected and directly subjected to differential scanning calorimetry testing. The specific testing method is as follows:
[0082] 5-10 mg of amorphous PETG copolyester samples were sampled and tested in a differential scanning calorimeter. The instrument parameters of the differential scanning calorimeter were set as follows: purge gas 1 (air): 0 mL / min; purge gas 2 (nitrogen) 40 mL / min; protective gas (nitrogen) 60 mL / min; temperature program: initial temperature 30°C, heating to 300°C at 10°C / min, once.
[0083] For detailed test results, see Figure 1 .
[0084] Figure 1 The results of direct differential scanning calorimetry testing of 11 amorphous PETG copolyester samples provided in this test example.
[0085] Depend on Figure 1 It can be seen that the differential scanning calorimetry (DSC) curve of PETG does not show crystallization and melting peaks, which means that the crystallization properties of amorphous PETG cannot be directly detected by differential scanning calorimetry.
[0086] (ii) The 11 amorphous PETG copolyester samples in the above step (i) were pre-treated according to the method of Example 1, and then the PETG polymer was precipitated for detection. The specific method is as follows:
[0087] 1. Sampling: Accurately weigh 1.0 g of 11 amorphous PETG copolyester samples and add 10 mL of hexafluoroisopropanol to each sample.
[0088] 2. Sample dissolution: Place on a heating plate and heat at 50°C for 1 hour and shake occasionally, then heat to 50°C and shake occasionally until completely dissolved, remove and let stand to cool to room temperature.
[0089] 3. Sample precipitation: Add 10 mL of methanol and mix thoroughly to precipitate the PETG polymer.
[0090] 4. Sample drying: Take out the precipitate and dry it in an oven at 100°C for 2 hours.
[0091] 5. Detection: Take 5-10 mg of sample and test it in differential scanning calorimeter. The instrument parameter settings of differential scanning calorimeter are as follows:
[0092] Set purge gas 1 (air): 0 mL / min if not turned on; purge gas 2 (nitrogen) 40 mL / min; protective gas (nitrogen) 60 mL / min;
[0093] Temperature program: initial temperature 30 °C, heating to 300 °C at 10 °C / min, one-time heating.
[0094] 6. Data processing: According to the melting peak temperature and its area, the crystallinity is calculated according to the following formula.
[0095] Xc = (melting peak area - cold crystallization peak area) / theoretical enthalpy of crystallization material * 100%.
[0096] Note: Xc is the crystallinity of the sample at different temperatures, and the theoretical enthalpy of the crystalline material is 140 J / g based on PET.
[0097] The differential scanning calorimetry (DSC) curves of 11 amorphous PETG copolyester samples treated by the pre-treatment method of the present application were detected.
[0098] Figure 2 This is a graph showing the results of differential scanning calorimetry testing of 11 amorphous PETG copolyester samples obtained by testing in the testing method of Example 1 provided in this test example.
[0099] Depend on Figure 2 It can be seen that the pre-treatment method of the present application can effectively release microscopic crystallinity information, and can be actually applied to the evaluation of high-transparency and high-brightness amorphous PETG polyester plastics.
[0100] Comparative Example 1
[0101] This comparative example is the same as Example 1 except that the "hexafluoroisopropanol" in the sampling of step 1 is replaced by "trifluoroethanol".
[0102] Comparative Example 2
[0103] This comparative example is the same as Example 1 except that the "hexafluoroisopropanol" in the sampling of step 1 is replaced by "o-cresol-chloroform mixed solution".
[0104] Comparative Example 3
[0105] This comparative example is the same as Example 1 except that the "hexafluoroisopropanol" in the sampling of step 1 is replaced by reagents such as "phenol-tetrachloroethane mixed solution".
[0106] The above comparative examples 1 to 3 were tested and found that some samples could not be completely dissolved and had compatibility problems with the solvent during methanol precipitation, and the microscopic crystallinity information of PETG could not be effectively released. In addition, the samples could not be dried quickly and had odor problems during drying.
[0107] Comparative Example 4
[0108] This comparative example is the same as Example 1 except that the "methanol" in the sample precipitation step 3 is replaced by acetonitrile solvent.
[0109] Comparative Example 5
[0110] This comparative example is the same as Example 1 except that the "methanol" in the sample precipitation step 3 is replaced by isopropanol solvent.
[0111] Comparative Example 6
[0112] This comparative example is the same as Example 1 except that the "methanol" in the sample precipitation in step 3 is replaced by tetrahydrofuran solvent.
[0113] The above comparative examples 4 to 6 were tested and found that, compared with methanol, although other solvents can also achieve the effect of precipitation after precipitation, other solvents increase the sample solubility to a certain extent, which will cause the sample to be dissolved by the solvent, resulting in the test results being different from the sample's own condition. The stronger the solvent solubility, the higher the crystallization temperature.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for testing microcrystallization of amorphous PETG copolyester, characterized in that: The test method includes: Pre-treating the amorphous PETG copolyester to obtain a test sample that can reflect the microcrystalline performance of the amorphous PETG copolyester, and then testing the test sample using differential scanning calorimetry; The pre-treatment method comprises: dissolving amorphous PETG copolyester in hexafluoroisopropanol, and then precipitating with methanol.
2. The testing method according to claim 1, characterized in that: The pre-treatment comprises the following steps: Amorphous PETG copolyester is added to hexafluoroisopropanol, and then heated to dissolve to obtain solution A; methanol is added to solution A to obtain a polymer precipitate; the polymer precipitate is dried to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
3. The testing method according to claim 2, characterized in that: The material-liquid ratio of amorphous PETG copolyester to hexafluoroisopropanol in the solution A is 0.5-1.5:5-15 g / ml.
4. The testing method according to claim 2, characterized in that: The temperature of the heating dissolution is (50-100)°C and the time is (0.5-2)h.
5. The testing method according to claim 2, characterized in that: The volume ratio of the added amount of methanol to solution A is (10-20):
5.
6. The testing method according to claim 2, characterized in that: The drying temperature of the polymer precipitation is (100-150)°C and the drying time is (0.5-2)h.
7. The testing method according to claim 1, characterized in that: The pre-treatment comprises the following steps: (A) adding amorphous PETG copolyester to hexafluoroisopropanol at a material-liquid ratio of 0.5-1.5:5-15 g / ml, and then heating and dissolving at 50° C. for 1 h to obtain solution A; (B) Methanol is added to solution A at a volume ratio of 10:5 to 15, and the mixture is stirred to obtain a solution containing a polymer precipitate, and the solid-liquid separation is performed. The polymer precipitate is dried at 100° C. for 2 h to obtain a test sample that can reflect the microcrystalline properties of amorphous PETG copolyester.
8. The testing method according to claim 1, characterized in that: The detection method of the differential scanning calorimetry comprises: The test samples were tested using a differential scanning calorimeter, and the crystallinity of the test samples was then calculated based on the melting peak temperature and melting peak area of the test samples.
9. The testing method according to claim 8, characterized in that: The crystallinity calculation formula of the test sample is: Crystallinity = melting peak area / theoretical enthalpy of crystalline material*100%.
10. The testing method according to claim 1, characterized in that: In the differential scanning calorimetry, the temperature is 30-300° C., and the heating rate is 10° C. / min.